Trajectories of marginal part-time work and risk of depression. Does job or income insecurity mediate the relation? - Nielsen, Helena Breth; Kirchheiner-Rasmussen, Jonas; Dyreborg, Johnny; Larsen, Ann Dyreborg; Madsen, Ida EH; Pedersen, Jacob; Garde, Anne Helene (Scandinavian Journal of Work, Environment & Health, 2023)
' ' OBJECTIVES ': 'Working few hours a week, known as marginal part-time work, may increase both job and income insecurity, which have been linked to the risk of depression. This study examines the association between marginal part-time work and depression and the mediating role of job and income insecurity. ' ' METHODS ': 'We included 30 523 respondents of the Danish Labor Force Survey (DLFS) between 2010 and 2017 and linked them to register-based information on weekly working hours, which was used to identify full-time workers and model group-based trajectories of marginal part-time. These data were linked with survey information on job and income insecurity, and register-based information on hospital-diagnosed depression or redeemed anti-depressant drugs in the following two years. We estimated hazard ratios (HR) by Cox proportional hazards models and conducted mediation analyses to estimate the natural direct and indirect effects using job and income insecurity as mediators. ' ' RESULTS ': 'We identified three distinct trajectories of marginal part-time work: constant marginal part-time work, mobile towards marginal part-time work, and fluctuating in and out of marginal part-time work. Compared with full-time workers, the constant [HR 2.42, 95% confidence interval (CI) 1.83–3.20], mobile (HR 2.84, 95% CI 2.16–3.75), and fluctuating (HR 3.51, 95% CI 2.07–5.97) trajectories all had higher risks of depression. There was no evidence of mediation by either job (HR 1.02, 95% CI 0.92–1.12) or income (HR 0.98, 95% CI 0.89–1.08) insecurity. ' ' CONCLUSIONS ': 'We found a higher risk of depression following marginal part-time work. The higher risk was not mediated by job or income insecurity.
Keywords: antidepressant; depression; income insecurity; job insecurity; marginal part-time work; mental health; part-time work; precarious employment; short working hour; trajectory; weekly working hour